PNLDC1, mouse pre‐piRNA Trimmer, is required for meiotic and post‐meiotic male germ cell development. (15th February 2018) - Nishimura, Toru; Nagamori, Ippei; Nakatani, Tsunetoshi; Izumi, Natsuko; Tomari, Yukihide; Kuramochi‐Miyagawa, Satomi; Nakano, Toru
Abstract: PIWI‐interacting RNAs (piRNAs) are germ cell‐specific small RNAs essential for retrotransposon gene silencing and male germ cell development. In piRNA biogenesis, the endonuclease MitoPLD/Zucchini cleaves long, single‐stranded RNAs to generate 5′ termini of precursor piRNAs (pre‐piRNAs) that are consecutively loaded into PIWI‐family proteins. Subsequently, these pre‐piRNAs are trimmed at their 3′‐end by an exonuclease called Trimmer. Recently, poly(A)‐specific ribonuclease‐like domain‐containing 1 (PNLDC1) was identified as the pre‐piRNA Trimmer in silkworms. However, the function of PNLDC1 in other species remains unknown. Here, we generate Pnldc1 mutant mice and analyze small RNAs in their testes. Our results demonstrate that mouse PNLDC1 functions in the trimming of both embryonic and post‐natal pre‐piRNAs. In addition, piRNA trimming defects in embryonic and post‐natal testes cause impaired DNA methylation and reduced MIWI expression, respectively. Phenotypically, both meiotic and post‐meiotic arrests are evident in the same individual Pnldc1 mutant mouse. The former and latter phenotypes are similar to those of MILI and MIWI mutant mice, respectively. Thus, PNLDC1‐mediated piRNA trimming is indispensable for the function of piRNAs throughout mouse spermatogenesis. Synopsis: PNLDC1 is the mouse Trimmer for piRNAs, a class of small non‐coding RNAs. PNLDC1 function is essential for the development of mouse male germ cells. Mouse PNLDC1 functions as pre‐piRNA Trimmer of both embryonic and postnatal piRNAs. piRNA trimming defects in embryonic and postnatal testes cause impaired DNA methylation and reduced MIWI expression, respectively. Two types of abnormalities at both meiotic and post‐meiotic stages are observed in the same individual Pnldc1 mutant mouse. Abstract : PNLDC1 is the mouse Trimmer for piRNAs, a class of small non‐coding RNAs. PNLDC1 function is essential for the development of mouse male germ cells.